(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of the article is to shed light on the peculiarities of the poetic skill and style of Usman Nasir. The poet’s poems are analyzed on the basis of autobiographical, comparative, historical and functional methods. Through the interpretation of the themes of love, childhood, homeland, the role and significance of Usman Nasir’s poetry in the Uzbek literature of the twentieth century was shown. A characteristic aspect of the sensual creative style is the harmonious expression of subtle emotions in the image of nature, something that, by analogy, comparison, comparison, enlivens, gives vitality, impressiveness to the image.